Roles and functions of special purpose vehicles (SPV): a comparison between Islamic and conventional finance / Mohammad Soleimani and S. Mustafa Shadab - Soleimani, Mohammad; Shadab, S. Mustafa (Universiti Teknologi Mara Selangor, 2020)
The SPV (special purpose vehicle) is one of the key components of the securitization in both Islamic and conventional finance; however the details of how the transactions are implemented differ subject to the mode of securitization in Islamic and conventional finance. In conventional finance, the bank establishes a SPV and transfers its asset from its balance sheet to the SPV. The assets are used as the collateral for issuing securitized, debt-like instruments. Nevertheless, in Islamic finance mode of securitization, the SPV just services the cash flows for security holders and do participate in debt-issuance. This difference is originated from the risk-sharing principle in asset-based Islamic finance which contrasts with risk-transfer nature of an interest-based conventional finance and results in important differences in ownership right and valuation of SPVs in the two financial systems.